2015
DOI: 10.1371/journal.pone.0121271
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Mutagenesis of Genes Encoding Predicted Autotransported Proteins of Burkholderia pseudomallei Identifies Factors Mediating Virulence in Mice, Net Intracellular Replication and a Novel Protein Conferring Serum Resistance

Abstract: Burkholderia pseudomallei is the causative agent of the severe tropical disease melioidosis, which commonly presents as sepsis. The B. pseudomallei K96243 genome encodes eleven predicted autotransporters, a diverse family of secreted and outer membrane proteins often associated with virulence. In a systematic study of these autotransporters, we constructed insertion mutants in each gene predicted to encode an autotransporter and assessed them for three pathogenesis-associated phenotypes: virulence in the BALB/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 53 publications
2
16
0
Order By: Relevance
“…Previous studies have examined the biological roles of all 8 ATs in B. pseudomallei (88)(89)(90). However, only the oligomeric ATs BimA (intracellular motility protein) (91), BoaA (92) and BpaC (93) (host cell adhesion proteins), and BpaB (biofilm and virulence factor) (77) have been functionally characterized in B. mallei.…”
mentioning
confidence: 99%
“…Previous studies have examined the biological roles of all 8 ATs in B. pseudomallei (88)(89)(90). However, only the oligomeric ATs BimA (intracellular motility protein) (91), BoaA (92) and BpaC (93) (host cell adhesion proteins), and BpaB (biofilm and virulence factor) (77) have been functionally characterized in B. mallei.…”
mentioning
confidence: 99%
“…The roles of these genes have already been reported. For example, bpss0796 encoding a putative trimeric autotransporter protein (BoaA) plays a role in survival of B. pseudomallei in macrophages (Balder et al, 2010), and a boaA mutant was attenuated in BALB/c mice (Lazar Adler et al, 2015). In addition, BPSS0796 is also identified as an immunogenic protein in melioidosis patient serum (Tiyawisutsri et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Burkholderia pseudomallei is a motile gram-negative pathogen that lives in dead organic matter in tropical and subtropical soils and water [56]. It causes melioidosis, which is a febrile illness with acute and chronic disease states with a high mortality rate.…”
Section: Trimeric Autotransporters Identified In B Pseudomallei Playmentioning
confidence: 99%
“…Consequently, autotransporters are important in the virulence of this pathogen, implying that they may be targets for vaccine development against other gramnegative bacteria in the future. Although the majority of autotransporters in B. pseudomallei play some role in the virulence of the pathogen, only the TAA BpaC seems not only to increase virulence, but also to protect against macrophages and enhance serum survival [56]. Lafontaine et al [61] showed in a series of adherence assays with human respiratory epithelial cells that deletion or overexpression of bpaC has different effects on the adhesion properties of the pathogen depending on the strain in which it is expressed.…”
Section: Trimeric Autotransporters Identified In B Pseudomallei Playmentioning
confidence: 99%